2020
DOI: 10.30534/ijatcse/2020/191932020
|View full text |Cite
|
Sign up to set email alerts
|

Optimize Volume for Planetary Gear Train by using Algorithm Based Artificial Immune System

Abstract: Planetary gear train (PGT) had widely used for power transmission in construction equipment and machinery. The main purpose of this paper is to present methods for minimize the volume of PGT as well as the minimum weight for space saving. This paper presents a comparison of develop algorithm based Artificial Immune System (AIS) to find the optimum combination of parameters design for minimize volume of two-stage PGT system. The developed algorithm is hybrid with Genetic Algorithm (GA) based AIS which named as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…These findings are supported by the observation of Srinivasan et al [28]. The significant of this study as shown that the time of cut increases also the energy consumption of the computer numerical control (CNC) machine, and the optimisation of the individual parameters will assist the time variation to reduce the energy consumption [29]. Al-Tawalbeh, and Feilat [30] shows that the power consumption in the economic system is very significant in sustainable development of manufacturing industry.…”
Section: Resultssupporting
confidence: 79%
“…These findings are supported by the observation of Srinivasan et al [28]. The significant of this study as shown that the time of cut increases also the energy consumption of the computer numerical control (CNC) machine, and the optimisation of the individual parameters will assist the time variation to reduce the energy consumption [29]. Al-Tawalbeh, and Feilat [30] shows that the power consumption in the economic system is very significant in sustainable development of manufacturing industry.…”
Section: Resultssupporting
confidence: 79%
“…6 Thus, these difficulties have driven the use of meta-heuristic optimizers for design optimization of planetary gears. [6][7][8]10,11,[13][14][15][16][17][18][19] Most of the studies in the literature are related to single-stage planetary gear sets and therefore there is a 1 literature gap for the volume minimization of multistage planetary gears. This study is conducted to measure the performance of recent nature-inspired methods in the design optimization of multistage planetary gear mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…6 Thus, these difficulties have driven the use of meta-heuristic optimizers for design optimization of planetary gears. 68,10,11,1319…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goal is to reduce the weight and power loss of the construction and produce gearbox with enhanced service life of the components. In this regard, in recent years a lot of research has been directed towards the optimal design of the gear trains [3,4]. In this way, researchers have considered the weight minimization of the single stage spur gears under the constraints, such as gear bending strength and shafts torsional strength [5].…”
Section: Introductionmentioning
confidence: 99%